UK/Canada Frontiers of Science: Artificial Intelligence Report - Vaishak Belle; Nicolas Papernot (FACETS)
In February 2024, the Frontiers of Science: Artificial Intelligence Conference was organized in Ottawa, Canada. It was a multidisciplinary meeting focused on early to mid-career researchers, a total of 40 researchers, half from Canada and the other half from the United Kingdom. This report briefly summarizes the objectives and outcomes from that meeting.